2021
DOI: 10.1590/0001-3765202120200860
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pyrimethanil fungicide on Chironomidae community structure

Abstract: The use of agrochemicals in agriculture may impact aquatic ecosystems, particularly infl uencing the stream insect communities. Among aquatic insects, the family Chironomidae is the most abundant and species-diverse insect group found in freshwater ecosystems. However, in the southern hemisphere, studies with Chironomidae are still sparse, compared to Europe and North America. The present study evaluates the responses of Chironomidae species (Insecta: Diptera) to pyrimethanil fungicide in a mesocosm experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Pyrimethanil exhibits a high antibacterial activity by inhibiting the synthesis and secretion of pathogenic hydrolase with systemic conduction and fumigation effects and has a fast degradation rate and a low residue level after use. 56,57 Propamocarb is a highly effective bactericide with local absorption, low toxicity, and low residue, and can be quickly decomposed by soil microorganisms. 58 To the best of our knowledge, all compounds obtained within the framework of this study are new compounds and have not been reported previously.…”
Section: Synthesis and Characterization Of Ilsmentioning
confidence: 99%
“…Pyrimethanil exhibits a high antibacterial activity by inhibiting the synthesis and secretion of pathogenic hydrolase with systemic conduction and fumigation effects and has a fast degradation rate and a low residue level after use. 56,57 Propamocarb is a highly effective bactericide with local absorption, low toxicity, and low residue, and can be quickly decomposed by soil microorganisms. 58 To the best of our knowledge, all compounds obtained within the framework of this study are new compounds and have not been reported previously.…”
Section: Synthesis and Characterization Of Ilsmentioning
confidence: 99%